SENSORY ANALYSIS OF COFFEE DRIED WITH AND WITHOUT STIRRING - Batista Ribeiro, Bruno; de Medeiros Câmara, Francisco Mickael; Guimarães Mendes, Antônio Nazareno; da Silva, Virgílio Anastácio; Faria Montanari, Fernanda (Coffee Science - ISSN 1984-3909, 2018)
The production of quality coffees, with different sensory characteristics, is strongly related to drying techniques. Experiments were carried out on coffee fruits, with the presence and absence of the fruit turnover process during drying in the yard, Catuaí Vermelho 144 coffee fruits, from the Cerrado Mineiro, processed dry and wet. The treatments consisted of natural parchment, natural green, peeled parchment and demucilated parchment fruits, which were dried in a concrete yard. They were conducted in a completely randomized design, with 4 post-harvest processes, 2 types of drying (with or without tillage) and 3 replications, totaling 24 plots. Natural green and natural parchment coffees were more responsive in the final scores, when not stirred during the drying process in the yard, unlike the coffees obtained by wet processing. Peeled coffees obtained the highest scores for the attributes, regardless of the adoption or not of stirring during the drying process in the yard. It was possible to obtain scores above 80 points by the SCA protocol, without stirring the coffee in the yard.